ANALISIS DAMPAK EKONOMI PROGRAM KELUARGA HARAPAN DI KECAMATAN UNGAR KABUPATEN KARIMUN - Saib, Nur Nadila Widiansa; Fitri Kurnianingsih; Okparizan (Regalia: Jurnal Riset Gender dan Anak, 2022)
Abstrack Poverty is a global phenomenon that is very proud for developing countries, especially Indonesian. One of the efforts to accelerate poverty reduction is to implement the Family Hope Program. The Family Hope Program is a conditional social assistance program given to poor families who are struggling to make ends meet. This study aims to identify the economic impact and inhibiting factors of the Family Hope Program in Ungar District, Karimun Regency. This study uses a descriptive qualitative approach using primary and secondary data sources, and data collection using observation, interviews, and documentation. The results of this study indicate that the Economic Impact of the Hopeful Family Program in Ungar Sub-district has not yet seen a maximum change, although the Hopeful Family Program has a positive impact on PKH recipients in helping to ease the necessities of life and reduce the burden. However, the PKH program was able to make economic changes that were slightly advanced as evidenced by the data that there were 17 PKH recipients who experienced changes before and after receiving assistance, while 154 other recipients were still in a condition of economic improvement. On the other hand, the PKH program has a negative impact, namely that there are still people who are dependent on government assistance. The inhibiting factor of the Family Hope Program is that there is data that is not accurate/not right on target because there are still poor people who have not received government assistance. Keywords: Analysis, Impact, Hopeful Family Program